A Review of Crippling Loss for Northern Bobwhites - Aaron M. Haines; Fidel Hernandez; Scott E. Henke; Ralph L. Bingham (National Quail Symposium Proceedings, 2017)
Many studies have reported estimates of crippling loss (i.e., birds shot, noticeably or not, and not retrieved) for northern bobwhites (Colinus virginianus); however, comparisons among studies have been difficult because of a lack of standardized definitions and methods of calculation. The purpose of this paper was to: 1) provide a review of crippling loss of bobwhites across their geographic range, and 2) develop terminology that allowed for explicit discussion of crippling loss and facilitated comparison among studies. We also obtained an estimate of crippling loss for bobwhites in southern Texas using data from a larger study investigating the effects of ranch-road baiting on bobwhites. Reported estimates of crippling loss ranged from 5 to 31% of recorded harvest and 5-24% of total kill. We propose that studies reporting crippling loss use explicit definitions including those developed herein, allowing for inter-study comparisons. Documenting crippling loss in the field should include monitoring of radio-marked bobwhites the morning after a hunt to correctly identify crippled loss birds. In addition, practices (e.g., amount of time spent looking for downed birds) potentially minimizing crippling loss on harvested bobwhite populations should be identified.
Keywords: crippling loss; harvest; northern bobwhite; population; Texas